Difficult-to-treat-pediatric Crohn's disease: focus on adalimumab - Zeisler B; Hyams JS (Dove Medical Press, 2015)
Bella Zeisler, Jeffrey S Hyams Division of Digestive Diseases, Hepatology, and Nutrition, Connecticut Children's Medical Center Hartford, University of Connecticut School of Medicine, Department of Pediatrics, Farmington, CT, USA Abstract: Adalimumab is a fully humanized anti-tumor necrosis factor alpha monoclonal antibody that was recently granted regulatory approval in the USA for the treatment of moderate to severe Crohn’s disease (CD) in children. Like infliximab, the first biologic agent used to treat pediatric CD, regulatory approval was secured many years following approval for adults. The long delay between adult and pediatric approval has led to many years of off-label use of adalimumab, although it is anticipated that the use of adalimumab may further increase with official regulatory approval. To date, pediatric literature on the use of adalimumab for treatment of CD is limited, and pediatric practitioners have mostly extrapolated from research and experience provided by the adult literature. The aim of this paper is to review the literature regarding adalimumab for the treatment of pediatric CD, and includes a review of landmark adult studies as well as the pivotal pediatric study that facilitated regulatory approval. We also discuss the role of anti-tumor necrosis factor alpha agents including adalimumab in the current treatment paradigm for pediatric CD. Keywords: pediatrics, Crohn's disease, adalimumab, biologic agent